Bacterial Sacroiliitis Probably Induced by Lumbar Epidural Analgesia - Shimon Edelstein; Yeouda Edoute (Hindawi Limited, 2003)
Background: Properly administered, lumbar epidural analgesia provides adequate pain relief during labor and delivery, and is considered to be a safe procedure with limited complications. The prevalence of infection after lumbar epidural analgesia is negligible.